Urban street design guide (Island Press/Center for Resource Economics Imprint: Island Press, 2013)
The NACTO Urban Street Design Guide shows how streets of every size can be reimagined and reoriented to prioritize safe driving and transit, biking, walking, and public activity. Unlike older, more conservative engineering manuals, this design guide emphasizes the core principle that urban streets are public places and have a larger role to play in communities than solely being conduits for traffic. The well-illustrated guide offers blueprints of street design from multiple perspectives, from the bird's eye view to granular details. Case studies from around the country clearly show how to implement best practices, as well as provide guidance for customizing design applications to a city's unique needs. Urban Street Design Guide outlines five goals and tenets of world-class street design: • Streets are public spaces. Streets play a much larger role in the public life of cities and communities than just thoroughfares for traffic. • Great streets are great for business. Well-designed streets generate higher revenues for businesses and higher values for homeowners. • Design for safety. Traffic engineers can and should design streets where people walking, parking, shopping, bicycling, working, and driving can cross paths safely. • Streets can be changed. Transportation engineers can work flexibly within the building envelope of a street. Many city streets were created in a different era and need to be reconfigured to meet new needs. • Act now! Implement projects quickly using temporary materials to help inform public decision making. Elaborating on these fundamental principles, the guide offers substantive direction for cities seeking to improve street design to create more inclusive, multi-modal urban environments. It is an exceptional resource for redesigning streets to serve the needs of 21st century cities, whose residents and visitors demand a variety of transportation options, safer streets, and vibrant community life.